2020
DOI: 10.1136/annrheumdis-2020-eular.4149
|View full text |Cite
|
Sign up to set email alerts
|

Ab0391 effect of HCQ on Lldas Achievement in Sle Patients

Abstract: Background:HCQ for SLE in Japan has been administered in many cases after approval. Therefore, the effect of additional administration of HCQ on low disease activity of SLE was considered to be clearer.Objectives:To clarify the effect of HCQ treatment on the control of disease activity in SLE patients.Methods:All SLE patients with low disease activity (LDA) enrolled in this study started additional HCQ treatment from January 2016. All patients with LDA enrolled in this study started HCQ treatment and had been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Meanwhile, several studies showed hydroxychloroquine(HCQ) has effect on reduction in lipids and thrombosis (1), but the mechanism is unclear. Objectives: We examined effect of HCQ on adipocytokine expression in SLE patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, several studies showed hydroxychloroquine(HCQ) has effect on reduction in lipids and thrombosis (1), but the mechanism is unclear. Objectives: We examined effect of HCQ on adipocytokine expression in SLE patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 Aswan University, Rheumatology and Rehabilitation, Aswan, Egypt; 2 Zagazig University, Rheumatology and Rehabilitation, Zagazig, Egypt Background: Cancer is known as one of the causes of morbidity and mortality in systemic lupus erythematosus (SLE) patients. It has been thought that SLE activity and stimulation of the immune system predisposes the risk of cancer (1). Objectives: To investigate the correlation between SLE disease activity and the cancer incidence.…”
Section: Discussionmentioning
confidence: 99%